Lest we remember? Recollection of the Boer War and Great War in Ireland - Ciarán WALLACE (E-REA)
Recalled memories are recalled from somewhere, and usually for some specific reason. After a generation of forgetting, Irish history has recalled the First World War and the participation of thousands of Irishmen in the service of the British Army. This recent burst of recollection has played a major role in the choreography of the peace process in Northern Ireland. Newly resurrected memory allows southern nationalists to join with northern unionists in commemorating an all-Ireland sacrifice. Nationalists can broaden their sense of nationhood to include those who fought in the ‘wrong’ war, and unionists can identify common values in their neighbours across the border. Historians, both professional and amateur, recovered this uncomfortable memory from beneath the foundation myth of the southern Irish state. From 1922 to the 1980s, official Irish history had prioritised the quasi-religious sacrifice of the Easter Rising in 1916 and the War of Independence which led to the foundation of the Irish Free State in 1922. The awkward fact that tens of thousands of Irishmen wore British uniforms in Europe, while hundreds of their countrymen fought against that same uniform in Dublin, received little coverage in school history texts. Even less space was given to the bitter Civil War which followed independence, as memories were allowed to cool and hopefully decay. This is not a straightforward account of forgetting and remembering, however, as an earlier conflict involving thousands of Dubliners has almost completely disappeared from popular Irish memory. Despite the existence of major monuments in the centre of Dublin, the memory of the South African or Boer War (1899-1902) has not attracted the same celebrity as the First World War. In relatively recent history, Irish troops in British uniform fought and died on a distant African battlefield. Intense coverage in the contemporary press, widespread public interest and profound grief (especially in Dublin city) marked the conflict out as a significant event, yet today it is forgotten. This article examines the very different forgetting and remembering applied to the South African and First World Wars. It addresses the political and social motivations for remembering. Using submerged memories in the built environment the article reflects on the space between remembering and forgetting; that national attic where histories are stored – just in case they are ever needed.